Introduction to the Tarikh of the Qur'an: Definition, Scope, and Urgency - Riska Candrayani; Rahmi Damis (TAFASIR: Journal of Quranic Studies, 2026)
This study aims to explore the contents of the Qur'an comprehensively through a study of Tārikh al-Qur'ān, including its definition, scope, and the urgency of historical studies of Tārīkh al-Qur'ān in Qur'anic studies. The research method used is a qualitative method with descriptive analysis and library research in data collection. The results of the study focus on the aspect of the meaning of Tarikh al-Qur'an, which is evidence of the systematic and collective preservation of the Qur'an. In addition, Tarikh al-Qur'an also explores the basic principles related to aspects of the journey of the Qur'an from a chronological, empirical, and documentary perspective. This study also highlights the importance of historical studies of the Qur'an as a scientific response to various Orientalist and modern thinkers who question the authenticity of the Qur'an.